2018
DOI: 10.1038/s41420-018-0109-7
|View full text |Cite|
|
Sign up to set email alerts
|

Zebrafish: an emerging real-time model system to study Alzheimer’s disease and neurospecific drug discovery

Abstract: Zebrafish (Danio rerio) is emerging as an increasingly successful model for translational research on human neurological disorders. In this review, we appraise the high degree of neurological and behavioural resemblance of zebrafish with humans. It is highly validated as a powerful vertebrate model for investigating human neurodegenerative diseases. The neuroanatomic and neurochemical pathways of zebrafish brain exhibit a profound resemblance with the human brain. Physiological, emotional and social behavioura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 200 publications
1
99
0
2
Order By: Relevance
“…However, expanding the range of experimental domains with the use of additional models, is now considered as an important strategy for translational neuroscience research (34). Recent data suggest zebra sh as an emerging successful model to study cognitive phenotypes and CNS related drug discovery (35)(36)(37). Accordingly, our behavioral results show that both GGRE and RE improved retention memory as indicated by the T-maze test.…”
Section: Discussionsupporting
confidence: 55%
“…However, expanding the range of experimental domains with the use of additional models, is now considered as an important strategy for translational neuroscience research (34). Recent data suggest zebra sh as an emerging successful model to study cognitive phenotypes and CNS related drug discovery (35)(36)(37). Accordingly, our behavioral results show that both GGRE and RE improved retention memory as indicated by the T-maze test.…”
Section: Discussionsupporting
confidence: 55%
“…Other advantages of the zebrafish model include rapid embryonic development, high fecundity, quite low housing and experimental costs [ 39 , 41 ]. Moreover, zebrafish possess a vertebrate neural structural organization and have already been established as a valuable model system to study alteration of astrocyte homeostasis in vivo [ 42 , 43 , 44 ], including astrogliosis [ 45 , 46 ]. It was found that zebrafish have two intracellular cobalamin-dependent enzymes, which share an overall amino acid identity with the corresponding human enzymes of approx.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, zebrafish and the human brain have a high conservation in the neuroanatomical structures [19,20] and neurochemical pathways [21]. The zebrafish forebrain medial, dorsal, and lateral pallium has strong similarities with the humans’ amygdala, isocortex, and hippocampus, respectively [22,23]. Moreover, despite the size difference of particular zebrafish brain structures, major brain components, such as the diencephalon or the cerebellum, are highly conserved with the human brain [24].…”
Section: Discussionmentioning
confidence: 99%